PENGARUH BUDAYA ORGANISASI DAN STRATEGI IMPLEMENTASI TERHADAP KEBERHASILAN MANAJEMEN PENGETAHUAN DI PT TELKOM - Sutarman Sutarman (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2007)
Knowledge Management Systems are expanding across all types of organizations worldwide. The competitive benefits of KM efforts have been demonstrated in industries, governments and in the academic worlds. However, recent global analyses of such implementations highlight the fact that not all of them are successful. The main barriers relate to organizational culture and theimportance of the implementation strategy. The purpose of this research is to explore relationships between the successful implementation of knowledge management and specific organizational cultural orientations and implementationstrategy. Organizational culture is assessed through organizational trust and organizational solidarity variables, in addition, through collecting and connecting strategy. Depending on the degree of integration of these two cultural and strategy factors determination, we demonstrated that specific KM are more or less likely to succeed. The research findings were accomplished through a validated questionnaire distributed within PT Telkom and their units. Though limited in terms of variable, this study has the potential to assist other researchers in refining and modifying such approaches to maximize knowledge in this field.